2023
DOI: 10.1021/acs.jmedchem.2c01772
|View full text |Cite
|
Sign up to set email alerts
|

Searching for Novel Noncovalent Nuclear Export Inhibitors through a Drug Repurposing Approach

Abstract: Chromosomal region maintenance protein 1 (CRM1) is a validated anticancer drug target, and its covalent inhibitor KPT-330 has been approved for marketing. However, the development of CRM1 inhibitors, especially the noncovalent ones, is still very limited. Drug repurposing is an effective strategy to develop drug leads for new targets. In this work, we virtually screened a library of marketed drugs and identified zafirlukast as a new CRM1 inhibitor. Biochemical and structural analysis revealed that zafirlukast … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Two previously reported noncovalent CRM1 inhibitors are insensitive to the CRM1 C528 mutation. 21,22 Here, the CRM1 C528S mutation partially impaired the activity of compounds in pull down and completely abolished the inhibitory effect of KL1 and KL2 on nuclear export (Figures S8 and S9). Structural analysis showed that C528 formed substantial hydrophobic interactions with aminoratjadone derivatives, regardless of compound hydrolysis (Figures 5C and S7).…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…Two previously reported noncovalent CRM1 inhibitors are insensitive to the CRM1 C528 mutation. 21,22 Here, the CRM1 C528S mutation partially impaired the activity of compounds in pull down and completely abolished the inhibitory effect of KL1 and KL2 on nuclear export (Figures S8 and S9). Structural analysis showed that C528 formed substantial hydrophobic interactions with aminoratjadone derivatives, regardless of compound hydrolysis (Figures 5C and S7).…”
Section: Resultsmentioning
confidence: 89%
“…In this work, we identified two novel CRM1 inhibitors, KL1 and KL2, that inhibited nuclear export much more potently than the reported noncovalent CRM1 inhibitors. 21,22 In most yeast species, the cysteine of CRM1 that is conjugated to LMB (1) is mutated to a threonine residue, which confers resistance to LMB (1) produced by neighboring competing cells. 27 Unlike LMB, the binding of several aminoratjadone derivatives to CRM1 did not rely on intermolecular covalent bonds.…”
Section: ■ Discussion and Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the plasticity of the NES groove and the high binding affinity of NES, the development of noncovalent inhibitors remains a considerable challenge. , We previously reported two noncovalent inhibitors, NCI-1 and zafirlukast, but these compounds suffered from problems such as low stability or low potency. , In this work, we discovered a series of novel noncovalent CRM1 inhibitors with a new scaffold by virtually screening a library of 1.4 million compounds. Structural and biochemical studies established the preliminary structure–activity relationship (SAR) of these compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Leptomycin B and KPT-330 are covalent inhibitors, whereas NCI-1 and zafirlukast are noncovalent inhibitors. The reported cell viability IC 50 values are indicated in the figure.…”
Section: Introductionmentioning
confidence: 99%